2019
DOI: 10.1038/s41386-019-0437-1
|View full text |Cite
|
Sign up to set email alerts
|

Early-life high-fat diet-induced obesity programs hippocampal development and cognitive functions via regulation of gut commensal Akkermansia muciniphila

Abstract: Obesity is one of the most serious public health challenges in the world. Obesity during early life has been associated with an increased risk of neurodevelopmental disorders, including deficits in learning and memory, yet the underlying mechanisms remain unclear. Here, we show that early life high-fat diet (HFD) feeding impairs hippocampus-dependent contextual/spatial learning and memory, and alters the gut microbiota, particularly by depleting Akkermansia muciniphila (A. muciniphila), in mice. Transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 47 publications
(84 reference statements)
11
92
0
1
Order By: Relevance
“…Most of these bacteria are already reported probiotics. The reduction of these bacteria may cause intestinal microenvironment disorders, and the intestinal mucosa barrier to resist external invasion will decrease, leading to increased susceptibility to carcinogenic factors [20][21]. After using DMH, the proportion of rumenococcus, Candida, Clostridium IV, and Enterobacter bacteria in the high-fat diet group decreased further, further indicating that the decrease in the proportion of these bacteria is an important cause of the increased intestinal susceptibility to carcinogens the reason.…”
Section: Discussionmentioning
confidence: 98%
“…Most of these bacteria are already reported probiotics. The reduction of these bacteria may cause intestinal microenvironment disorders, and the intestinal mucosa barrier to resist external invasion will decrease, leading to increased susceptibility to carcinogenic factors [20][21]. After using DMH, the proportion of rumenococcus, Candida, Clostridium IV, and Enterobacter bacteria in the high-fat diet group decreased further, further indicating that the decrease in the proportion of these bacteria is an important cause of the increased intestinal susceptibility to carcinogens the reason.…”
Section: Discussionmentioning
confidence: 98%
“…It is widely accepted that gut microbiota dysbiosis was correlated with the development and progress of AD. [ 28 ] The microbial diversity was decreased in AD participants, including reduced ACE, Chao1, and Shannon index. [ 18 ] AR‐C17 treatment could modulate the abundance of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that oral treatment of Akkermansia could modulate gut permeability, reduce neuroinflammation, and restore neuronal function, thus ameliorating cognitive deficits in HFD‐fed mice. [ 28 ] Meanwhile, Lactobacillus consumption could improve physiological function and cognitive ability of aged mice. [ 30 ] Moreover, Clostridium are positively associated with obesity, insulin resistance, and AD development.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia associated with obesity, cardiovascular disease, low‐grade inflammation, and gut microbiota dysbiosis is considered a vital risk health factor to human. [ 1 ] Numerous drugs have been permitted for the treatment of hypercholesterolemia. Nevertheless, many of these drugs have been withdrawn attributed to severe side‐effects, such as easy rebound, heart diseases, reduction of body immunity, and other disorders.…”
Section: Introductionmentioning
confidence: 99%